Identification of Nitrite, Borax, and Formaldehyde Content of Homemade Pork Sausages in Pontianak City Market - Permadi, Edy; Suciati, Fitri; Alfius, Musa (Jurnal Sain Peternakan Indonesia, 2024)
Meat is one of the animal-based food products produced by livestock such as beef cattle, goats, chickens, and pigs. It is generally processed into several products, such as sausages, meatballs, salami, corned beef, jerky, and nuggets. Most meat-processed products industries use food additives such as nitrites to improve the quality of the products. This research aims to determine residual nitrites content in pork sausage and the detection of prohibited food additives, such as borax and formaldehyde. This research used qualitative and quantitative test methods. The data obtained was statistically analyzed using descriptive analysis. The samples used were 10 homemade pork sausages marketed in Pontianak City Market. The parameters observed were nitrite content, borax, and formaldehyde qualitative detection. The research showed four samples of 10 homemade pork sausages in Pontianak City Market were higher than the permissible range (< 30 µg/g) of residual nitrites. Meanwhile, the borax and formaldehyde detection tests showed that all the samples of homemade pork sausages containing borax and formaldehyde were detected negative. To provide food safety, education on nitrites and the regulation regarding food additives is needed for the homemade pork sausage producers in Pontianak City Market. Hence, consumers are protected from the harmful effects of nitrites, borax, and formaldehyde.